2018
DOI: 10.12681/mms.15951
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Quality Status of the Algiers coastal waters by using macroalgae assemblages as bioindicators (Algeria, Mediterranean Sea)

Abstract: Macroalgal assemblages have been used as a quality element for the assessment of the ecological status classes (ESCs) in coastal water bodies for the implementation of the European Water Framework Directive (WFD, 2000/60/EC). To assess the suitability of this quality element in the coastal waters off Algiers, seven sampling sites with five (5) replications covering a wide range of anthropogenic pressures were studied during spring and summer 2015. Coverage data for the macroalgae at each sampling site were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The correlation matrix showed significant correlations between the four biotic indices. Finally, the EQR score for the current survey (0.55) was similar to the EQR scores reported by Chabane et al (2018) (0.41) and Bahbah et al (2020) (0.49), who used macroalgal assemblages that are known to be good indicators of water quality (Ballesteros et al, 1984;Bishop et al, 2002;Arévalo et al, 2007;Orlando-Bonaca et al, 2008;Lasinio et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…The correlation matrix showed significant correlations between the four biotic indices. Finally, the EQR score for the current survey (0.55) was similar to the EQR scores reported by Chabane et al (2018) (0.41) and Bahbah et al (2020) (0.49), who used macroalgal assemblages that are known to be good indicators of water quality (Ballesteros et al, 1984;Bishop et al, 2002;Arévalo et al, 2007;Orlando-Bonaca et al, 2008;Lasinio et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…More research gaps that need to be addressed include long-term in-depth environmental evaluations. Macroinvertebrates and macroalgae may be applied as ecological indicators for water quality assessment and overall aquatic ecosystem health [ 96 , 97 ]. However, current research on water quality after implementation of a revetment is rare.…”
Section: A Way Forwards To Protect Coastlines With Revetmentsmentioning
confidence: 99%

Environmental impacts of shore revetment

Sanitwong-Na-Ayutthaya,
Saengsupavanich,
Ariffin
et al. 2023
Heliyon
“…In another study performed at the Algerian coast Grimes (2010) have reported similar results. This analysis makes it possible to relativize the current environmental situation of the studied sites compared to states of disturbance more important present on some Algerian waters (Rouane-Hacene et al, 2017;Belhaouari et al, 2017;Khadidja et al, 2018).…”
Section: Faunistic Analysis and Ecological Indexmentioning
confidence: 99%